VD_FINDINFO Arrêt / 2017 / 475 vom 2. Juni 2017 - VD Tribunal cantonal (2017)
FARDEAU DE LA PREUVE, COMPÉTENCE, RADIATION DU RÔLE | 40 al. 1 LPGA, 58 al. 1 LPGA, 58 al. 3 LPGA, 60 al. 1 LPGA, 94 al. 1 let. a LPA-VD, 94 al. 1 let. c LPA-VD